Effect of pressure change on microleakage of different sealing materials - Abdelrahman Ossama Elmekkawi; Alaa Eldin Hussein Youssif Diab; Mohammed Hassan Elsabry (Cairo : Abdelrahman Ossama Elmekkawi, 2010)
This in vitro study was carried out to evaluate effect of a therapeutic pressure to which the patients is subjected in the treating pressure chambers on the apical microleakage of the enhodontically treated teeth sealed using either ZOE silicon and resin based sealers . The crowns of sixty frehly extracted single rooted human teeth removed at the level of CEJ
Thesis (M.Sc.) - Cairo University - Faculty of Oral and dental Medicine - Department of Endoodontics
Issued also as CD
Keywords: Compression capsule; Hyperbaric oxygen therapy; Microleakage